The β Pictoris association: Catalog of photometric rotational periods of low-mass members and candidate members - Messina, S. (2017)
Aims. We intended to compile the most complete catalog of bona fide members and candidate members of the β Pictoris association, and to measure their rotation periods and basic properties from our own observations, public archives, and exploring the literature. Methods. We carried out a multi-observatories campaign to get our own photometric time series and collected all archived public photometric data time series for the stars in our catalog. Each time series was analyzed with the Lomb-Scargle and CLEAN periodograms to search for the stellar rotation periods. We complemented the measured rotational properties with detailed information on multiplicity, membership, and projected rotational velocity available in the literature and discussed star by star. Results. We measured the rotation periods of 112 out of 117 among bona fide members and candidate members of the β Pictoris association and, whenever possible, we also measured the luminosity, radius, and inclination of the stellar rotation axis. This represents to date the largest catalog of rotation periods of any young loose stellar association. Conclusions. We provided an extensive catalog of rotation periods together with other relevant basic properties useful to explore a number of open issues, such as the causes of spread of rotation periods among coeval stars, evolution of angular momentum, and lithium-rotation connection.